The Additive Effects of Type-2 Diabetes on Cognitive Function in Older Adults with Heart Failure - Alosco, Michael L. (Hindawi Publishing Corporation, 2012)
Background. Medical comorbidity has been theorized to contribute to cognitive impairment in heart failure (HF) patients. Specifically, type-2 diabetes mellitus (T2DM), a common coexisting condition among HF patients, may be an independent predictor of cognitive impairment. Nonetheless, the relationships between T2DM and other risk factors for cognitive impairment among persons with HF are unclear. Methods. Persons with HF (N = 169, 34.3% women, age 68.57 ± 10.28 years) completed neuropsychological testing within a framework of an ongoing study. History of T2DM, along with other medical characteristics, was ascertained through a review of participants' medical charts and self-report. Results. Many participants (34.9%) had a comorbid T2DM diagnosis. After adjustment for demographic and medical characteristics, HF patients with T2DM evidenced significantly greater impairments across multiple cognitive domains than HF patients without T2DM: λ = .92, F(5, 156) = 2.82, P = .018. Post hoc tests revealed significant associations between T2DM and attention (P = .003), executive function (P = .032), and motor functioning (P = .008). Conclusion. The findings suggest additive contributions of T2DM and HF to impairments in attention, executive function, and motor function. Future work is needed to elucidate the mechanisms by which T2DM exacerbates cognitive impairment in HF.